Entry and competition in freight transport: the case of a prospective transalpine rail link between France and Italy - Delphine Prady; Hannes Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
We analyze the expected effects of building a rail tunnel between Lyon and Turin on i) the market shares of the established and the new suppliers, and ii) consumer surplus. The prospective project consists of a 53km rail tunnel providing freight shippers with a new alpine path. We calibrate an equilibrium model where freight shippers choose a mode and alpine path to ship goods from a given origin to a given destination. Freight carriers strategically set prices for the differentiated products they supply. Deriving the market equilibrium, we simulate the entry of a quality-improved product and test its competitive viability. The prospective alpine path proves both competitive and welfare-enhancing on the regional market, loses its competitive edge on the wider North-South market, and leads to a modal shift on the West-East market. We argue that the new infrastructure is only one tool out of a global modal shift-oriented policy toolbox.
Keywords: R41; L92; H54; L13; C63; 330; Transalpine freight; New rail infrastructure; Simulation model; Competition; Tunnel; Güterverkehr; Verkehrsteilung; Wettbewerb; Marktanteil; Konsumentenrente; Frankreich; Italien; Alpen